Pediatric Intensive Care: Immunomodulation With Activated Protein C ex vivo - Hassan O. Eliwan; Hassan O. Eliwan; Hassan O. Eliwan; Hassan O. Eliwan; William R. G. Watson; Irene Regan; Brian Philbin; Fiona M. O'Hare; Fiona M. O'Hare; Fiona M. O'Hare; Tammy Strickland; Amanda O'Neill; et al. (Frontiers Media S.A., 2019)
Objective: Sepsis is major cause of morbidity and mortality in the Pediatric Intensive Care Unit (PICU). PICU patients may develop transient immune deficiency during sepsis. Activated Protein C (APC) has significant anti-inflammatory and cytoprotective effects. Clinical trials of APC in adult sepsis initially showed improved outcome but recent trials showed no benefit in adults or children. We aimed to assess the effects of APC treatment on innate immune responses in children.Design and Subjects: We compared neutrophil and monocyte responses to lipopolysaccharide (LPS) with and without APC treatment in PICU patients at the time of evaluation for sepsis compared with healthy adults and age-matched pediatric controls. We used flow cytometry to examine cell activation (CD11b expression), function [intracellular reactive oxygen intermediate (ROI) release] and LPS recognition [Toll like Receptor 4 (TLR4) expression].Results: PICU patients had significantly decreased protein c levels and LPS responses compared with adult and pediatric controls for all parameters. APC reduced LPS-induced neutrophil PICU TLR4 and adult ROI (p < 0.05). PICU non-survivors had increased LPS induced neutrophil and monocyte ROI production vs. survivors which was significantly reduced by APC.Conclusion: PICU patients demonstrate significantly reduced endotoxin reactivity which may predispose them to sepsis and alter effective antibacterial responses. APC reduces LPS-induced ROI production in adults and may have a role in treating severely compromised PICU patients especially given that newer APC forms are associated with decreased bleeding risk and enhanced anti-inflammatory effects.